Comparative evaluation of dexmedetomidine, tramadol, and dexamethasone in prevention of post-spinal shivering in lower limb orthopedic surgeries - Loveleen Kour; Disha Dogra; Santosh Gupta; Tanvi Gupta (Asian Journal of Medical Sciences, 2025)
Background: Shivering is a commonly encountered post-anesthesia event. Tramadol is an easily available drug that is often used to prevent shivering. However, its side effects like nausea have prompted the search for better dugs that could prevent shivering with minimal side effects. Aims and Objectives: Our study aimed at comparing the efficacy of tramadol, dexmedetomidine, and dexamethasone in preventing post-spinal shivering in lower limb orthopedic surgeries. Materials and Methods: A total of 90 patients were enrolled for this study and divided into three groups – group Dx-received 1 μg/kg of dexmedetomidine, group De-received 0.1 mg/kg of dexamethasone, and group T-received 0.5 mg/kg of tramadol. Incidence of shivering was the primary outcome. Secondary outcomes were-shivering score, sedation score, hemodynamic parameters, and adverse effects, if any. One-way analysis of variance was employed for comparing continuous variables and the Chi-square test for categorical variables. Results: Incidence of shivering and shivering score was the least in dexmedetomidine group, followed by tramadol and dexamethasone. Sedation score was higher with dexmedetomidine than tramadol and dexamethasone. Conclusion: Dexmedetomidine is most effective in preventing post-spinal shivering in patients. The sedation it caused added comfort to the patients for the duration of surgery and did not cause any significant adverse effect in post-operative period.